Air Quality Monitoring System using IoT - J. SriramPavan, CH. Himabindu, K.C.K.Naik, K.G.S.Venkatesan (Mathematical Statistician and Engineering Applications, 2023)
The main agenda of our project Air Quality Monitoring System, is to measure the quality of air using MQ135, MQ2 and MQ7 sensors. By monitoring air quality, the general population becomes more conscious of the value of leading healthier lives for future generations. The Indian government has previously taken steps to outlaw the use of motorbikes with single and two-stroke engines since they contribute significantly to air pollution. We are working to design a plan for putting the air quality monitoring system in place. Due to the increase of automobiles on the road today, as well as the effects of industry and urbanization, air pollution has become one of the major problems. There are negative effects on prosperity from this rise in pollution levels. This project illustrates how an Air Quality Monitoring system is represented and carried out. The innovation understood here is a practical application of the Internet of Things concept. The job is completed using an Arduino microcontroller board. In this project, we’re going to build an IOT-based air quality monitoring system. To do this, we’ll use an ESP8266 Wi-Fi device to monitor the air quality over a web server, and we’ll show the Amount of dangerous gases like CO2, CO, and ammonia in PPM (Parts Per Million)